Italian nationwide survey on Pseudomonas aeruginosa from invasive infections: activity of ceftolozane/tazobactam and comparators, and molecular epidemiology of carbapenemase producers. (5th December 2017) - Giani, Tommaso; Arena, Fabio; Pollini, Simona; Di Pilato, Vincenzo; D'Andrea, Marco Maria; Henrici De Angelis, Lucia; Bassetti, Matteo; Rossolini, Gian Maria; ,
Abstract: Objectives: Pseudomonas aeruginosa is a major cause of severe healthcare-associated infections and often shows MDR phenotypes. Ceftolozane/tazobactam is a new cephalosporin/β-lactamase inhibitor combination with potent activity against P. aeruginosa . This survey was carried out to evaluate the susceptibility of P. aeruginosa, circulating in Italy, to ceftolozane/tazobactam and comparators and to investigate the molecular epidemiology of carbapenemase-producing strains. Methods: Consecutive non-replicate P. aeruginosa clinical isolates (935) from bloodstream infections and lower respiratory tract infections were collected from 20 centres distributed across Italy from September 2013 to November 2014. Antimicrobial susceptibility testing was performed by broth microdilution and results were interpreted according to the EUCAST breakpoints. Isolates resistant to ceftolozane/tazobactam were investigated for carbapenemase genes by PCR, and for carbapenemase activity by spectrophotometric assay. WGS using an Illumina platform was performed on carbapenemase-producing isolates. Results: Ceftolozane/tazobactam was the most active molecule, retaining activity against 90.9% of P. aeruginosa isolates, followed by amikacin (88.0% susceptibility) and colistin (84.7% susceptibility). Overall, 48 isolates (5.1%) were positive for carbapenemase genes, including bla VIM ( n = 32), bla IMP ( n = 12) and bla GES-5 ( n = 4), while the remaining ceftolozane/tazobactam-resistant isolates tested negative for carbapenemase production. Carbapenemase producers belonged to 10 different STs, with ST175 ( n = 12) and ST621 ( n = 11) being the most common lineages. Genome analysis revealed different trajectories of spread for the different carbapenemase genes. Conclusions: Ceftolozane/tazobactam exhibited potent in vitro activity against P. aeruginosa causing invasive infections in Italy. Carbapenemase production was the most common mechanism of resistance to ceftolozane/tazobactam.